If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1 = 11 + 5x Reorder the terms: -1 + X = 11 + 5x Solving -1 + X = 11 + 5x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + X = 11 + 1 + 5x Combine like terms: -1 + 1 = 0 0 + X = 11 + 1 + 5x X = 11 + 1 + 5x Combine like terms: 11 + 1 = 12 X = 12 + 5x Simplifying X = 12 + 5x
| 2y^3-2y^2-6y-10=0 | | 15x-7[x+2]=5x-2 | | X-.33x=25000 | | -68-(-25)= | | N+1=3n+9 | | (xy)dx+(x+1)dy=0 | | 0.95x+0.05(2-x)=0.10(163) | | 4z^2-4x=24 | | 12 = k2 + 10 | | 72x^2-8x+9=0 | | 3.5+(-7.5)= | | -1-6p=6-7p | | n-9-9n=1-7n | | 7=2g+3 | | 6+6n=-4(2-5n) | | 3.5+(7.5)= | | 28-6x=49-9x | | (X+1)=x | | 14y+41=139 | | 0.33333333333(21-3a)=6-a | | 3x+2x-11=84 | | 6x+0.4=6.4 | | -2x-18=-(1-2x)+4x | | 4(a+2)=14-2(3-a) | | 4n=5-5n | | 88=12x-44 | | 16x-16-8x-12=3 | | 9-4b=4-3b-6b | | 16-(2x-3)=6 | | 6x-14=2(3x-72) | | 11x-13=5(2x+4)-7 | | 45=29-2(x-3) |